Improved Mechanical Amplification of Monolithic PZT and PZT Composite via Optimized Honeycomb Macrostructures - Eichhorn, Franziska; Bytomski, Julia; Gerauer, Markus; Kakimoto, Ken Ichi; Fey, Tobias (Materials, 2022)
Honeycomb-based, modular composites with a relative density of 0.3948 and a slenderness ratio Lges/t of 6.48 were fabricated on PZT building blocks connected with a PZT-filled phenyl silicone resin. The macro- and micro-structure, phase composition, and the interface between the two materials were analyzed by SEM and image analysis techniques. The mechanical in-plane strain response was determined with uniaxial compression tests and the transversal piezoelectric strain response was determined by applying an electric field. These deformations were analyzed by a 2D digital image correlation analysis to calculate the mechanical strain amplification of monolithic and composite PZT lattice structures. Compared to bulk PZT, the piezoelectric strain amplification in the Y-direction |aypiezo| was higher by a factor of 69 for the composite and by a factor of 12 for the monolithic cellular PZT lattice, when it was assumed that the ratio of the deformation of the bulk material to bulk material was 1. The mechanical amplification of the composite lattices increased up to 73 and that of the cellular PZT lattices decreased to 12. Special focus was given to the fracture behavior and the interface of the PZT/PZT-filled phenyl silicone resin interface.
CRIS-Team Scopus Importer:2022-12-09
Keywords: cellular solid; ceramic composites; ceramics-functional; ceramics-structural; functionalization; piezoceramic composites; piezoelectric materials; strain amplification